Effect of drying parameters on the formation of early and intermediate stage products of the Maillard reaction in different plum (Prunus domestica L.) cultivars. (January 2016) - Michalska, Anna; Honke, Joanna; Łysiak, Grzegorz; Andlauer, Wilfried
Abstract: Four plum cultivars grown in Poland were freeze-dried (FD) and tunnel-dried (TD; 40 °C, 60 °C, 85 °C) and the impact of the drying processes on selected bioactive compounds, antioxidant capacity (ABTS radical scavenging assay; FRAP reducing test) and the progress of Maillard reaction was compared. The emphasis was laid on the early and intermediate stage of the Maillard reaction. Compared to fresh plums, the dried ones contained less available lysine and total sugars. Furosine (2-furoylmethyl-lysine) formation was increased by higher drying temperature. The highest level of ε-N-carboxymethyl-l -lysine (CML) and fluorescent intermediary compounds was noted after TD at 60 °C proving that the progress of the Maillard reaction in plums is strictly dependent on the process temperature. Application of 40 °C seems to prevent the decrease in the nutritional value of dried plums by inhibiting the further formation of adverse MRPs. Assessment of the formation of early and intermediate products of the Maillard reaction during the drying of plums is a useful tool for the evaluation of their nutritional quality. Highlights: Plum drying caused changes in phenolics, anthocyanins and antioxidant capacity. The available lysine and total sugar content decreased after plum drying. The formation of furosine in plums was dependent on drying conditions. The formation of carboxymethyllysine in plums was dependent on drying conditions. Fluorescent intermediary compounds were formed during the drying of plums.